Nitrogen fertilizer driven nitrous and nitric oxide production is decoupled from microbial genetic potential in low carbon, semi-arid soil - McDonald, Mark D.; Lewis, Katie L.; DeLaune, Paul B.; Hux, Brian A.; Boutton, Thomas W.; Gentry, Terry J. (Frontiers in Soil Science, 2023)
Nitrous oxide (N2O) emission from soil is a major concern due to its contribution to global climate change and its function as a loss mechanism of plant-available nitrogen (N) from the soil. This is especially true in intensive agricultural soils with high rates of N fertilizer application such as those on the semi-arid Southern High Plains, USA. This study examined emissions of N2O, pore-space concentrations of N2O and nitric oxide (NO), soil chemical properties, water content, and the genetic potential for N cycling five years after conservation system and N management implementation. For these semi-arid soils with low N, carbon, and water contents, large soil N2O emissions (up to 8 mL N2O-N m-2 day-1) are directly related to the application of N fertilizer which overwhelms the N2O reducing capacity of the soil. When this fertilizer N is depleted, N2O flux is either low, non-existent, or net-negative and has been observed as early as mid-season for preplant applied N fertilizer (-0.1 mL N2O-N m-2 day-1). Soil pore-space gas concentrations (N2O and NO) remained relatively constant across the growing season (average N2O: 0.78 µL N2O L-1 soil air; NO: 3.3 µL NO L-1 soil air, indicating a base-level of N-cycle activity, but was not directly related to surface emissions of N2O which decreased across the growing season. In addition, genetic potential for N cycle activities increased across the growing season simultaneously with stagnant/reduced N cycle activity. This reflects the difficulty in relating genetic potential to in-situ¬ activity in field research. It is likely that in a nutrient and carbon-poor soil, such as the semi-arid agricultural soil in this study, the microbial processes associated with N cycling are mostly limited by inorganic-N and less directly related to genetic potential at the time of sampling.